The pattem of the conquest of the Polabian Slavs and Western Baltic lands from the point of view of Christianization of the Baltic tribes - Marius Ščavinskas (Lietuvos Istorijos Studijos)
In the article there is the comparison of the pattern of the conquest of the Polabian tribes (including Polish Pomeranian areas) to that one of the Western Baltic tribes. Chronologically the conquest of the Polabian Slavic lands began already during the period of the first dynasty of Otton-Liudolfings (the first half of the 10th century), but the occupation itself, however, was over only in the middle of the 12th century. The lands of the Polabian Slavs were the target of occupation not only for the Saxons, but for Denmark and Poland as well (11th-12th centuries). Poland targeted all its energy towards the conquest of the Polish Pomeranian areas meanwhile Denmark, especially from the beginning of the 11th century, was trying to take hold of the Southern Seaside of the Baltic Sea. All these conquests had several important characteristics in common: 1) the establishment of the institutions of church and their incorporation into the church layers of the conquerors; 2) the implementation of the fiscal policy in the conquered lands; 3) the demand for the conquered tribes to observe the norms of Christian life, not separating this from the obedience to the conquerors.